2010
DOI: 10.1007/s11916-009-0092-z
|View full text |Cite
|
Sign up to set email alerts
|

Current Developments in Intraspinal Agents for Cancer and Noncancer Pain

Abstract: Since the late 1980s, intrathecal (IT) analgesic therapy has improved, and implantable IT drug delivery devices have become increasingly sophisticated. Physicians and patients now have myriad more options for agents and their combination, as well as for refining their delivery. As recently as 2007, The Polyanalgesic Consensus Conference of expert panelists updated its algorithm for drug selection in IT polyanalgesia. We review this algorithm and the emerging therapy included. This article provides an update on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…The pump is currently in clinical trials to assess the pressure sensor. [ 77 ] In most of the current drug delivery devices, failure is determined only when the patient has shown physical side effects. …”
Section: Mems Dosing Control Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pump is currently in clinical trials to assess the pressure sensor. [ 77 ] In most of the current drug delivery devices, failure is determined only when the patient has shown physical side effects. …”
Section: Mems Dosing Control Systemsmentioning
confidence: 99%
“…Olive, NJ), utilizes a positive pressure gas expansion actuation design with battery powered valves for fl ow regulation ( Figure 28 ). [ 77 ] The device is intended for chronic pain management and delivers morphine into intrathecal space with a fl ow rate of up to 28 mL per day [ 103 ] (overall 97.5% dose accuracy). The 20 mL fi xed-volume reservoir is refi llable.…”
Section: Prometramentioning
confidence: 99%
“…Smalldiameter A-delta and C fibers primarily transmit nociceptive information. 13 Second-order neurons in the dorsal horn possess a wide variety of neurotransmitter receptors. The excitatory amino acid, glutamate, is also present within small-diameter primary afferents and can be released by noxious stimulation, resulting in the activation of second-order neurons in the dorsal horn of the spinal cord.…”
Section: Peripheral Nerve Neurotransmitters and The Spinal Cordmentioning
confidence: 99%
“…The duration of sensory blockade was prolonged in the group receiving midazolam by over 25 minutes without increasing motor blockade. 13 Prochazka and associates 81 injected doses of 0.02 to 0.06 mg/kg into 14 patients with 10 administrations or more and reported that none of them displayed any clinical signs of neurotoxicity, such as bladder or bowel dysfunction, motor or sensory deficits, or new neuropathic pain. 79 Other studies have found intrathecal midazolam to be effective in treating chronic mechanical low back pain, musculoskeletal pain, and neurogenic pain.…”
Section: Box 434 Intrathecal Gabaergic Medicationsmentioning
confidence: 99%
See 1 more Smart Citation